1990
DOI: 10.1200/jco.1990.8.6.956
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin for the treatment of anemia of malignancy associated with neoplastic bone marrow infiltration.

Abstract: This clinical trial was performed to study the effects of intravenously (IV) administered recombinant human (rh) erythropoietin (EPO) at escalating doses (150, 300, and 450 U/kg, administered as an IV bolus injection, twice weekly, for 6, 4, and 4 weeks, respectively) in five patients with low-grade non-Hodgkin's lymphoma (Ig NHL) and bone marrow involvement and one patient with multiple myeloma (MM). All patients were anemic due to underlying disease. None of the patients had a history of bleeding, hemolysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(35 citation statements)
references
References 12 publications
5
30
0
Order By: Relevance
“…In fact in our study two out of the three non responder patients presented the lowest levels of pretreatment serum erythropoietin. These data are consistent also with the reports by Ludwig (1990) and Oster (1990). The findings of the present study show the effectiveness and the safety of subcutaneous administration of rHuEPO even with a lower dose respect to that demonstrated effective by intravenous route.…”
Section: Discussionsupporting
confidence: 93%
“…In fact in our study two out of the three non responder patients presented the lowest levels of pretreatment serum erythropoietin. These data are consistent also with the reports by Ludwig (1990) and Oster (1990). The findings of the present study show the effectiveness and the safety of subcutaneous administration of rHuEPO even with a lower dose respect to that demonstrated effective by intravenous route.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with published data suggesting that in chronic lymphoproliferative disorders, anemia is not only related to the bone marrow infiltration by the neoplastic clone [23, 24]. …”
Section: Discussionsupporting
confidence: 83%
“…Chronic administration at 3 !Jg/ kg/ day for up to nine weeks did not sustain the increase in four of five patients. Vadhan-Raj et al (64) reported similar results when giving recombi-nant human GM-CSF by continuou s intravenous infusion for 28 days as two 14 day cycles with a two week rest interval. One patient in U1e first study progressed to acute leukemia after two doses of recombinant human GM-CSF.…”
supporting
confidence: 59%